Reflections of Heritage in the Traditional Costumery of The Dusun Tindal of Sabah - Salbiah Kindoyop; Noria ak Tugang; Humin Jusilin; Nurul Aisyah Othman (2018)
The design and accessories of the Dusun Tindal traditional costume reveal an intricate relationship between the materials used and the community’s view of life. The practice of showcasing their traditional costume during festivals and ceremonies reflect the Dusun Tindal community’s commitment towards preserving their culture and heritage. This study explores the culture related to the designs of Dusun Tindal traditional costumes with specific focus on the community residing at the id Nuluhon (hill land area), a village located close to the foothill of Mount Kinabalu. This study, based on field work activities conducted in id Nuluhon, examines the structural design and presentation of the sinuranga (for men) and rinagang (for women) in the Dusun Tindal traditional costumery